Enzymatic hydrolysis of cellulose banana stem (alkaline microwave-assisted pre-treatment) - Samara, Faras Saskia; Novia, Novia; Melwita, Elda (Journal of Integrated and Advanced Engineering (JIAE), 2024)
The banana stem waste holds immense promise as a readily available and abundant source of lignocellulosic biomass, making it a compelling alternative for biofuel and biochemical applications. Therefore, this study focuses on investigating the impact of both time and substrate loading on the enzymatic hydrolysis of banana stem cellulose that has undergone alkaline microwave-assisted pre-treatment. The pre-treatment method involves subjecting the biomass to 5% KOH for 30 min, followed by microwave exposure at 300 W for 5 min, a process aimed at enhancing the accessibility of cellulose. Enzymatic hydrolysis experiments were carried out utilizing cellulase enzymes derived from Aspergillus niger, with variations in hydrolysis times (ranging from 5 to 45 h) and enzyme-to-substrate ratios (ranging from 1:1 to 1:10). The results of this investigation revealed a substantial improvement in hydrolysis efficiency, owing to the synergistic effects of alkaline microwave-assisted pre-treatment, signifying enhanced cellulose accessibility. Notably, the highest concentration of reducing sugars (1.3 mg mL−1) was achieved at a substrate-to-enzyme ratio of 1:1 and a hydrolysis duration of 45 h. These findings provide valuable insights into the conversion of lignocellulosic biomass, emphasizing the potential of integrated pre-treatment strategies for sustainable biorefinery applications. This research contributes to advancing our understanding of lignocellulosic biomass utilization, offering a promising avenue for biofuel and biochemical production from banana stem waste.